2018
DOI: 10.1002/etep.2688
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of winding MMF harmonic reduction methods in IPM machines equipped with FSCWs

Abstract: Summary In this paper, implementation of fractional‐slot concentrated windings (FSCWs) into an interior permanent magnet (IPM) machine, designed by using the same geometrical and operational specifications as Toyota Prius 2010 IPM machine, has been presented. In detail, the Toyota Prius's IPM equipped with integer‐slot distributed windings has been considered as a reference machine. Then the geometry of the stator has been adequately modified in other five models to equip FSCWs and adopt different magnetomotiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It has also been revealed that for small power applications, it might me be more reasonable to use FSCW topology because of the moderate output power with high efficiency. However, as shown in [2,3] for large power application, since a large amount of the cooling equipment might be required because of the large eddy current induced in the rotor part. In addition, excessive eddy currents can further lead to a high rotor temperature particularly at high speeds, and hence the rotor magnets will suffer from a high risk of irreversible demagnetisation [29,30,45,46].…”
Section: Power Losses and Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been revealed that for small power applications, it might me be more reasonable to use FSCW topology because of the moderate output power with high efficiency. However, as shown in [2,3] for large power application, since a large amount of the cooling equipment might be required because of the large eddy current induced in the rotor part. In addition, excessive eddy currents can further lead to a high rotor temperature particularly at high speeds, and hence the rotor magnets will suffer from a high risk of irreversible demagnetisation [29,30,45,46].…”
Section: Power Losses and Efficiencymentioning
confidence: 99%
“…Therefore, reduction of copper loss can be achieved by optimising the design for maximum efficiency (very limited improvement), implying various magnetomotive force (MMF) reduction methods, such as flux-barriers, different number of turns per phase, phase shifting etc. [2] or introducing a new winding topology having very short-end windings with very low MMF harmonic content. In [3], a new winding topology, called novel semi-overlapped winding (NSW), has been introduced by presenting the influence of winding parameters on the performance characteristics and merits/demerits of the proposed winding by comparing the electromagnetic performance characteristics of the interior permanent-magnet machines (IPMs) having different winding topologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of reducing the end‐winding axial length is to decrease the most dominant machine loss, which typically is the stator copper loss, and to decrease the total axial length to reduce the space requirement (promote compactness) of the electrical machines. The most recent performance improvement methods related to electrical machine windings have been listed as follows. Multi‐layer fractional‐slot concentrated windings (FSCWs) and integer slot concentric windings with phase‐shifted and un‐even number of turns per coil side [7–19, 38–41]. In addition, FSCWs having more than two layers [9, 11, 16–19, 29–31, 33, 39].…”
Section: Introductionmentioning
confidence: 99%
“…AFPM machine is one of the best candidates for use in many applications such as renewable energy applications, electromechanical traction drives, electric cars, and marine propulsion system. Regarding the number of stator and rotor discs, AFPM machines are classified into three categories: single‐sided structure, double‐sided structure, and multi‐stage structure . The double‐sided type is the most widely used type of AFPM motor .…”
Section: Introductionmentioning
confidence: 99%